2019
DOI: 10.1108/ijccsm-03-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Households’ perception of flood risk and health impact of exposure to flooding in flood-prone informal settlements in the coastal city of Mombasa

Abstract: Purpose Mombasa City in Kenya is one of the most vulnerable towns to flood risk due to its low-lying coastal location. Those at the highest risk in the city are households living in the flood-prone informal settlements. However, little is known about the perception of these vulnerable households to the flood risks and its health impacts, which is important for developing effective long-term adaptation strategies. The purpose of this paper is to examine the general perception of the residents regarding flood ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…In the study areas, 68.1% of the households were at low educational status (illiterate, functional adult literate and grade 1–4) which is relatively consistent with the finding of Amare et al (2020) that showed above 50% of respondents’ illiteracy indicating the strong commitment of enhancing people’s awareness for better coping-capacity against vulnerabilities. Contrarywise, respondents’ educational level was inconsistent with the report of Okaka and Odhiambo (2019) that discloses the secondary level of education for above 50% of the households. Farmland is also among the basic characteristics of the households.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the study areas, 68.1% of the households were at low educational status (illiterate, functional adult literate and grade 1–4) which is relatively consistent with the finding of Amare et al (2020) that showed above 50% of respondents’ illiteracy indicating the strong commitment of enhancing people’s awareness for better coping-capacity against vulnerabilities. Contrarywise, respondents’ educational level was inconsistent with the report of Okaka and Odhiambo (2019) that discloses the secondary level of education for above 50% of the households. Farmland is also among the basic characteristics of the households.…”
Section: Resultsmentioning
confidence: 78%
“…Risk perception, as scientifically evidenced, is among the factors that strongly affect household-level adaptation strategies against natural hazards. In Africa, the flood-prone city dwellers are reported as well-cognizant of vulnerabilities with such attributes (Okaka and Odhiambo, 2019). Moreover, perception of risk is claimed to be changeable through time per the occurring natural hazards manifested with the differential magnitude of vulnerability (Balteanu et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A person who has experienced natural disasters has a significant impact on his/her risk perception. Persons with past flood experience and flood knowledge education are quite sensible to flood risk perception (Okaka and Odhiambo, 2019). The fear of experiencing an earthquake positively and indirectly affects the risk perception of earthquake survivors (Bronfman et al, 2020).…”
Section: Disaster Knowledgementioning
confidence: 99%
“…Vulnerability to water scarcity is perceived differentially in rural India as a result of location, farm size, level of income, and with lesser degree by demographic attributes like age, sex, and education (Singh et al 2018). Risk perception, as scienti cally evidenced, is among the factors that strongly affect household level adaptation strategies against natural hazards where ood prone African city dwellers are well cognizant of their vulnerability (Okaka and Odhiambo 2019). Others on the other hand state that perceiving risk is changeable through time in accordance with the occurring natural hazards and variations in people's perception take place as a result of differential magnitude of vulnerability with socioeconomic characteristics (Balteanu et al 2014).…”
Section: Introductionmentioning
confidence: 99%